Effect of health education on gallstone disease among Uygur rural residents in Xinjiang Production and Construction Corps: evaluation on a two years intervention program - Xi-xi QIN; Ru-lin MA; Heng GUO (Editorial Office of Chinese Journal of Public Health, 2023)
Objective To evaluate intervention effect of health education on gallstone disease in Uygur rural residents of Xinjiang Production and Construction Corps (Xinjiang Corps) , and to provide a reference for the prevention and control of gallstone disease in the population. MethodsThe participants of the study were adult ( ≥ 18 years) Uygur people residing at least one year in four randomly-selected rural areas (two as intervention group and two as control group) under administrative of Xinjiang Corps. A 2-year gallstone disease-related health education program (including publicity of basic knowledge, on-site consultation, dissemination of propaganda materials in Uygur and Chinese, and lectures of 30-minutes long every 3 - 4 months) was conducted only among the participants in intervention group. With a self-designed questionnaire on gallstone disease related knowledge, attitude and practice (KAP), two waves of face-to-face interview were performed among 1 612 participants of intervention group and 744 controls before the intervention during June - July 2019 and 799 intervened participants and 580 controls by the end of intervention during July - September 2021. The status and changes of KAP about gallstone disease among the participants of intervention and control groups were analyzed and compared. ResultsBefore the intervention, there were no significant differences in total score and dimensional scores of KAP between the intervention group and the control group (all P > 0.05). After the intervention, significantly higher total KAP score (3.02 ± 4.23 vs. 1.79 ± 2.89) and scores of knowledge (1.53 ± 2.21 vs. 0.88 ± 1.53), attitude (0.98 ± 1.35 vs. 0.61 ± 1.04) and practice (0.52 ± 1.08 vs. 0.30 ± 0.92) were observed among the intervened participants compared to those in the controls (all P < 0.01). After the intervention, significantly higher proportions of intervened participants reported being aware of general knowledge (12.6% vs. 7.4%), with appropriate attitude (14.0% vs. 8.6%) and adopting healthy behaviors (7.4% vs. 4.3%) about gallstone disease in comparison with the controls (all P < 0.05) but there were no significant differences in the proportions between the intervention group and control group before the intervention (all P > 0.05). Conclusion The health education program effectively improved the knowledge, attitude and practice about gallstone disease among rural Uygur residents in Xinjiang Corps.